SDSS-IV MaNGA: spatially resolved star formation in barred galaxies. Issue 4 (22nd May 2020) - Fraser-McKelvie, Amelia; Aragón-Salamanca, Alfonso; Merrifield, Michael; Masters, Karen; Nair, Preethi; Emsellem, Eric; Kraljic, Katarina; Krishnarao, Dhanesh; Andrews, Brett H; Drory, Niv; Neumann, Justus
ABSTRACT: Bars inhabit the majority of local-Universe disc galaxies and may be important drivers of galaxy evolution through the redistribution of gas and angular momentum within discs. We investigate the star formation and gas properties of bars in galaxies spanning a wide range of masses, environments, and star formation rates using the Mapping Nearby Galaxies at APO galaxy survey. Using a robustly defined sample of 684 barred galaxies, we find that fractional (or scaled) bar length correlates with the host's offset from the star formation main sequence. Considering the morphology of the Hα emission we separate barred galaxies into different categories, including barred, ringed, and central configurations, together with Hα detected at the ends of a bar. We find that only low-mass galaxies host star formation along their bars, and that this is located predominantly at the leading edge of the bar itself. Our results are supported by recent simulations of massive galaxies, which show that the position of star formation within a bar is regulated by a combination of shear forces, turbulence, and gas flows. We conclude that the physical properties of a bar are mostly governed by the existing stellar mass of the host galaxy, but that they also play an important role in the galaxy's ongoing star formation.